Micronutrient policy change in South Africa: Implications for the Kaleidoscope Model for food security policy change - Hendriks, Sheryl L.; Mkandawire, Elizabeth; Hall, Nicolette; Olivier, Nic JJ; Schönfeldt; Hettie C.; Randall, Phillip; Morgan, Stephan; Haggblade, Steven; Babu, Suresh Chandra (Michigan State University, 2017)
This review of micronutrient policy processes in South Africa serves as a companion piece to two parallel studies in Malawi and Zambia. All three studies employ the Kaleidoscope Model of policy change to trace the causal forces leading to key micronutrient policy decisions in each of the three countries. After outlining the overall micronutrient policy process in South Africa, the study focuses on policy decisions regarding vitamin A supplementation, fortification with iodine, iron and multinutrient fortificant, and the reduction of sodium in foods. The analysis in this paper traces the evolution of policies in the pre- and post-apartheid periods through to the present time. In addition to a substantive review of published and grey literature on micronutrient status and policies in South Africa, the research team conducted semi-structured interviews with 15 policy stakeholders in South Africa between October 2015 and June 2016 using a standardised interview guide.